Air-cooled adsorption-based device for harvesting water from island air. (May 2021) - Wang, Wenwen; Xie, Sitao; Pan, Quanwen; Dai, Yanjun; Wang, Ruzhu; Ge, Tianshu
Abstract: Adsorption-based, atmospheric water harvesting is a promising method for addressing water scarcity, which is a common issue in island areas, which often contain a large amount of fresh water in the air. Most existing adsorption-based atmospheric water harvesting systems usually require an additional cooling source, e.g., water-cooling, to cool the released humid high-temperature air below its dew point to harvest liquid water. To date, large-scale atmospheric water harvesting devices that use air cooling in such conditions have not yet been developed. Herein, we report a forced air-cooled proof-of-concept device for harvesting water from island air. Fabricated using 21 kg activated carbon fibre felt (ACFF)–silica sol–LiCl30, this device generated up to 7.7 kg of water (adsorption at 31 °C with 63% relative humidity) per day-and-night cycle, with a thermal efficiency (ratio of thermal energy to water conversion) of 0.37, using air cooling alone in laboratory-simulated island conditions. This study verifies the possibility of using air cooling to condense released humid air. It provides a flexible water generation solution for island regions with limited supplies of fresh water and power. Highlights: A large-scale air-cooled atmosphere water generator was constructed and tested. The device delivered 7.7 kg water and achieved a thermal efficiency of 0.37. Equilibria and dynamic properties of the composite adsorbents were characterized. Heat energy can be provided by solar energy or other renewable energy sources. Adsorption–desorption cycle could help space heating and sustainable agriculture.